Efektivitas Model Permainan Kartu Indeks (Index Card Match) Terhadap Hasil Pembelajaran Perkembangan Kognitif Dan Sosial Emosional Anak Usia 5-6 Tahun Di TK Al-Harits - Fatmawati Fatmawati (Institut Agama Islam Negeri Madura, 2021)
This study aims to determine the effectiveness, index card match card game. Cognitive and emotional development of children aged 5-6 years at TK AL-Harits. Using qualitative methods and data collection techniques using interviews and direct field observations and observations of events that occur in the field. The population is all children as many as 40 people. The data analysis used was phenomenal analysis with interviews and observations for children and teachers. The results showed that the effectiveness, index card match card game Cognitive and emotional development of children aged 5-6 years can form a child's mindset in solving a problem and be more sensitive in making a decision for himself and on his own wishes in the form of examples, practices, and responsibilities. from the teacher. It can be concluded that with this index card game children can make their independence in solving a problem that occurs to themselves and children are more responsible for the decisions that have been made by themselves.